American datu : John J. Pershing and counterinsurgency warfare in the Muslim Philippines, 1899-1913 - Edgerton, Ronald K., 1942- (Battles and campaigns (Lexington, Ky.), 2020)
"Public support for the Philippine-American War effort in 1901 was high. America was quickly gaining victory over the insurrecting Filipinos, with only a few pockets of resistance remaining; however, snuffing out the resistance proved more difficult than American leaders expected. Soon, news of extreme violence used against the Filipinos began to fill every newspaper. Reports relayed surprise attacks resulting in excessive carnage and instances of American generals ordering troops to kill every native over the age of 10. Inevitably, American public support of the war quickly waned. President Theodore Roosevelt knew he had to respond swiftly. Enter John J. Pershing, a man widely recognized as the most progressive, the most knowledgeable, and the most broadly experienced military official imaginable. With such a reputation, Roosevelt knew Pershing was the perfect man to secure a more palatable victory in the Philippines. During the final decade of the Philippine conflict, Pershing forged deep bonds with the Moro people, and by doing so helped bring the war to a more peaceful end. In American Datu, Ronald K. Edgerton follows Pershing through his attempt to gain military control over the region without attracting negative news coverage. Edgerton details every advancement of this mission: from Pershing's progressive guerrilla tactics, to his efforts to build relationships with the Moro leaders, to the lasting impact of his approach to US counterinsurgency doctrine. He also addresses the important role the Philippine-American War played in developing America's military strategy in the twentieth and twenty-first centuries, and argues that modern approaches are inferior to Pershing's balanced and realistic methods"--